Effective Behavioral Strategies for Managing ADHD in Children: A Comprehensive Review - Veena Shivanna; Yogeesh Mallenahalli Chikkanna (Disease and Health Research - New Insights Vol. 1, 2024)
Attention deficit hyperactive disorder is the most common psychiatric disorder seen in children in which the child expresses inattentiveness and hyperactivity as the core behaviour characteristics. It affects about 4-12% of all school-age children and is also among the most prevalent chronic psychological condition affecting school-aged children. Managing a child diagnosed with ADHD is quite challenging regardless of the situation presented. Behavioural techniques for managing a child with ADHD are not intuitive for most parents and teachers. It is futile and damaging to try to force a child with ADHD to be like most children. It is possible, however, to limit destructive behaviour and to instil in the child a sense of self-worth that will help overcome negativity. This review article encompasses various techniques for managing a child with ADHD under different practical scenarios and guides parents, teachers and also clinicians to accommodate and modify the behaviour of the child, which includes nondrug therapies, dietary changes, cognitive behavioral therapy, the importance of zinc and other behavioural approaches to manage and modify the child with ADHD.